ARTIFICIAL INTELLIGENCE, LAW AND THE 2030 AGENDA FOR SUSTAINABLE DEVELOPMENT: INTELIGÊNCIA ARTIFICIAL, DIREITO E A AGENDA 2030 PARA O DESENVOLVIMENTO SUSTENTÁVEL - Divino, Sthéfano Bruno Santos (Caderno de Relações Internacionais, 2021)
This paper has the following research problem: how can Artificial Intelligence (AI) contribute to the achievement of the goals of Agenda 2030 for Sustainable Development? In order to satisfy the problem, the first section aims to address the relationship between AI and SDG. Among the objectives that can be most influenced by technologies, both positively and negatively, are the SDG’s that have water, health, agriculture, and education as their guideline. This approach will be achieved through the description and demonstration of reports provided by the United Nations Educational, Scientific, and Cultural Organization (UNESCO). The second section of the report criticizes the reduction or eradication of adverse effects that AI can have on society. A case study from countries such as China, the United Kingdom, and Canada is used as a guideline since they have a strong influence on the scenario addressed. To this end, deductive and integrated research methods are used, as well as the technique of case study research. In the end, it is shown that AI is an essential factor in the equation posed by Agenda 2030, provided it is duly observed and regulated. Bibliographical research and the integrated research method will be used.